2017
DOI: 10.18697/ajfand.80.16550
|View full text |Cite
|
Sign up to set email alerts
|

Effect of different stress treatments on mature green tomatoes (Solanum lycopersicum) to enhance fruit quality

Abstract: Tomato (Solanum lycopersicum) is a crop of immense economic importance and is grown worldwide. Its fruit is of great nutritional importance as it forms a major part of human diet. Global production of tomato has been estimated at over 153 million metric tonnes in 2009. Consumption of tomato is believed to benefit the heart among other things, as it contains lycopene, one of the most powerful natural antioxidants. The present study was conducted to find the effect of multiple stresses; salt, mannitol, drought a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 14 publications
1
2
0
Order By: Relevance
“…Total soluble solids (TSS), total sugar, reducing sugar, and β-carotene content were significantly influenced by salinity and various levels of Ca alone or in combination ( Table 5 ). These findings are consistent with many other researchers [ 20 , 51 , 54 , 56 , 82 , 83 , 84 ]. Salinity has positively improved the TSS and other organic compounds, which might be due to increased accumulation of Na + , K + and chorine (Cl − ) ions in fruit [ 56 ].…”
Section: Discussionsupporting
confidence: 94%
“…Total soluble solids (TSS), total sugar, reducing sugar, and β-carotene content were significantly influenced by salinity and various levels of Ca alone or in combination ( Table 5 ). These findings are consistent with many other researchers [ 20 , 51 , 54 , 56 , 82 , 83 , 84 ]. Salinity has positively improved the TSS and other organic compounds, which might be due to increased accumulation of Na + , K + and chorine (Cl − ) ions in fruit [ 56 ].…”
Section: Discussionsupporting
confidence: 94%
“…(2014) reported that lycopene content may increase in tomato fruits grown in greenhouses under water deficiency conditions. Drought application was found to significantly increase the lycopene content in tomatoes (Klunklin & Savage, 2017; Randome et al ., 2017).…”
Section: Resultsmentioning
confidence: 99%
“…It is versatile in consumption as a fresh or processed vegetable, and it is an excellent dietary source of antioxidant compounds, vitamins A, C, E, and carotenoids, with beneficial effects on human health, making it popular worldwide. Therefore, it is a promising candidate for biofertilization with plant probiotics ( Randome et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%